Cavernous hemangioma presenting during pregnancy: A detailed literature review - Ranger, Adrianna; Grigenas, Orest; Labib, Mohamed; Avery, Michael; Lownie, Stephen P. (Journal of Pediatric Neurology, 2011)
Cavernous hemangiomas (CH) are occult vascular malformations, typically presenting as hemorrhage within a cerebral hemisphere, or as seizures. Brainstem and cerebellar locations of these lesions are less commonly described. Potentially very serious, they tend to result in severe deficits or death. We review the existing scientific literature on their presentation and course during pregnancy. Relevant cases were identified through electronic searches of multiple internet search databases, including PubMed, SciSearch, Scientific Commons, Springer Link, and Google, using advanced search functions and multiple search terms, using both American and British spellings. Detailed literature review revealed, including our own single case, 26 patients, ranging from 15 to 37 years, with 28 episodes of CH presenting during pregnancy. Two thirds occurred in the third trimester. Supratentorial lesions all presented with seizures, but without neurological deficits or documented hemorrhage, and all patients did well. Conversely, infratentorial lesions always presented with neurological deficits, usually with hemorrhage and never with seizures, and outcomes were quite variable, including maternal and fetal deaths. CHs are rare in pregnancy, but can affect pregnant women of any age, tending to occur in the 3rd trimester. Supratentorial CH present with seizures and patients generally do well. CH within the brainstem present with hemorrhage, and such patients have a guarded prognosis. If far enough into gestation, immediate delivery of the fetus and resection of the lesion are recommended.
Keywords: Brainstem; cavernous hemangioma; intracranial hemorrhage; pregnancy; seizure